2020
DOI: 10.17650/2222-1468-2020-10-1-93-100
|View full text |Cite
|
Sign up to set email alerts
|

Stratification of papillary thyroid cancer relapse risk based on the results of molecular genetic studies

Abstract: Introduction. Post-transcriptional mechanisms play a crucial role in the biological course and clinical manifestations of papillary thyroid cancer (PTC). Recent studies show that an increased content of oncogenic or reduced content of oncosuppressive microRNAs increases the aggressiveness of the tumor and correlates with an unfavorable prognosis of treatment, which allows them to be used in personalizing the treatment tactics of patients with PTC. The study objective is to compare the level of expression of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…We examined 11 different miRNAs in preoperative cytology specimens and demonstrated that expression levels of two of them (miRNA-146b and miRNA-221) were significantly increased in the subgroups of patients having such features as regional metastases and extrathyroidal extension. The present work confirmed the findings of our previous study, where the expression levels of these same miRNAs were evaluated using postoperative specimens and the high risk of PTC recurrence was 9.7 times more probable (95% CI 3.1-29.5) if miR-221 level was > 1.0 [31].…”
Section: Discussionsupporting
confidence: 91%
“…We examined 11 different miRNAs in preoperative cytology specimens and demonstrated that expression levels of two of them (miRNA-146b and miRNA-221) were significantly increased in the subgroups of patients having such features as regional metastases and extrathyroidal extension. The present work confirmed the findings of our previous study, where the expression levels of these same miRNAs were evaluated using postoperative specimens and the high risk of PTC recurrence was 9.7 times more probable (95% CI 3.1-29.5) if miR-221 level was > 1.0 [31].…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, increased expression of miR-221, which is not typical for FTC in general, is one of the main features of HCC ( Figure 3 ). This factor probably determines the more aggressive behavior of HCC; this hypothesis applies if we extrapolate the PTC data to HCC [ 43 ].…”
Section: Discussionmentioning
confidence: 99%